Mineral composition and gemological characteristics of the fossil marine reptiles of the Ulyanovsk region - D. A. Petrochenkov (Известия высших учебных заведений: Геология и разведка)
Fossils of marine reptiles are a new jewelry and ornamental material and collected in the Ulyanovsk region from the Upper Jurassic deposits. They consist of (wt. %): calcite — 52, apatite — 24 and pyrite — 23, and also gypsum presents. The contents of radioactive and carcinogenic elements are close to background. The original bone structure of reptiles is preserved. Apatite replaces the bone tissue of marine reptiles, forming a cellular framework. According to the chemical composition, apatite refers to fluorohydroxyapatite with an increased Sr content. The size of the crystals is finely-dispersed. Calcite and pyrite fill the central parts of the cells. Calcite crystals of isometric and elongated shape, 0,01—0,05 mm in size, form blocks up to 0,3 mm during intergrowth. Calcite fills thin, discontinuous veins along the contour of cells with a width of up to 0,03 mm. In calcite, among the impurity elements, there are (wt. %, on the average): Mg — 0,30, Mn — 0,39 and Fe — 0,96. Pyrite forms a dispersed impregnation in calcite and apatite, content of impurities is, wt. %: Ni — up to 0,96 and Cu — up to 0,24. On technological and decorative characteristics of fossils of sea reptiles of Ulyanovsk region are qualitative jewelry and ornamental materials of biomineral group, allowing to make a wide assortment of jewelry and souvenir products.